The Histone Acetyltransferase Gcn5 Regulates ncRNA-ICR1 and FLO11 Expression during Pseudohyphal Development in Saccharomyces cerevisiae - Wang, Long-Chi (Hindawi Publishing Corporation, 2015)

(untitled) (Biomed Res Int)
Filamentous growth is one of the key features of pathogenic fungi during the early infectious phase. The pseudohyphal development of yeast Saccharomyces cerevisiae shares similar characteristics with hyphae elongation in pathogenic fungi. The expression of FLO11 is essential for adhesive growth and filament formation in yeast and is governed by a multilayered transcriptional network. Here we discovered a role for the histone acetyltransferase general control nonderepressible 5 (Gcn5) in regulating FLO11-mediated pseudohyphal growth. The expression patterns of FLO11 were distinct in haploid and diploid yeast under amino acid starvation induced by 3-amino-1,2,4-triazole (3AT). In diploids, FLO11 expression was substantially induced at a very early stage of pseudohyphal development and decreased quickly, but in haploids, it was gradually induced. Furthermore, the transcription factor Gcn4 was recruited to the Sfl1-Flo8 toggle sites at the FLO11 promoter under 3AT treatment. Moreover, the histone acetylase activity of Gcn5 was required for FLO11 induction. Finally, Gcn5 functioned as a negative regulator of the noncoding RNA ICR1, which is known to suppress FLO11 expression. Gcn5 plays an important role in the regulatory network of FLO11 expression via Gcn4 by downregulating ICR1 expression, which derepresses FLO11 for promoting pseudohyphal development.